A study on method of prevention for timber defects on traditional Malay house / Cik Noraza Hazirah Cik Azli - Cik Azli, Cik Noraza Hazirah (Faculty of Architecture, Planning and Surveying, 2015)
This study was carried out to describe the method of prevention for timber defects on Traditional Malay House. This study focused on prevention method which it is part of conservation process. The study is aimed to prolong the heritage timber houses life and maintain its significance such as historical value, architecture value and economy for future generation. The objectives are to identify types of timbers and its uses for traditional house, to observe defects occur on conserved traditional house and to identify method of prevention for timber defects on traditional house. Several methods have been used, interview session and observation, in order to achieve the objectives of the study. The interview is conducted among the respective persons from case study, parties involved, Perbadanan Muzium Melaka (PERZIM) and Badan Warisan Malaysia (BWM). The result from the observation shows that the conserved timber buildings are well-being care where it can be clearly seen only minor defect occurred during observation. The method of prevention for timber defect is done and it is compliance with the standard.